Wall-less Flow Phantoms with 3D printed Soluble Filament for Ultrasonic Experiments - Huber, Christian; Lyer, Stefan; Ermert, Helmut; Heim, Christian; Rupitsch, Stefan J.; Ullmann, Ingrid (Current Directions in Biomedical Engineering, 2023)
Tissue-mimicking materials (TMMs) typically used for ultrasound phantoms include gelatin, agarose and polyvinyl alcohol (PVA). These materials have shown sufficient similarity in ultrasound parameters compared to human tissue. Despite their extensive use for years to generate ultrasound phantoms, no simple and easily reproducible way to generate complex, wall-less ultrasound flow phantoms has been introduced. Commercially available ultrasound flow phantoms are limited to simple flow geometries that do not reflect the complex blood flow in humans. Flow phantoms with complex geometries presented in scientific publications either have walls between TMMs and the flow channel, are limited to one material, or are complicated to produce. In this contribution, we present a method using 3D printing and soluble filament that allows for the reliable and consistent production of complex flow geometries with the typical materials used for ultrasound phantoms and without any walls.
CRIS-Team Scopus Importer:2023-10-20
Keywords: 3D Printing; Flow Experiments; Ultrasound; Ultrasound Phantoms